ROLES AND CHALLENGES OF MUSLIM WOMEN IN THE DEVELOPMENT OF HEALTHCARE SECTOR IN NASARAWA STATE - Hashiya Ahmad; Sa’adatu Hassan Liman (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
The paper examines the role and challenges of Nigeria women in the development of the health sector, focusing on Muslim women of Nasarawa state, Nigeria. Women assist in the provision of healthcare; they play roles which complement those of men. Some women are physicians’ that is medical doctors, nurses and top hospital administrators. Women however are mostly concentrated in the low status health-related occupations such as hospital maids, nurses, and other paramedical jobs. The paper begins by conceptualising some basic concepts such as health sector and women for a better understanding. This is followed by the geographical location of the Nasarawa state. This study also assesses the roles of Muslim women in the health sector both in the conventional and in traditional. These include supportive systems to help women realise their professional or career goals. Interview and desk review were adopted as method of data collection for the research, where in-depth interview was conducted with some personalities. It is concluded in the paper that there is the need for sensitization of the Muslim community in the state on importance of Muslim women involvement in the healthcare profession.